Solvent and Media Effects on the Photophysics of Naphthoxazole Derivatives - Encina-Rojas, M (2013)
The photophysical properties of 2-phenyl-naphtho[1,2-d][1,3]oxazole, 2(4-N,N-dimethylaminophenyl)naphtho[1,2-d][1,3]oxazole and 2(4-N,N- diphenylaminophenyl) naphtho[1,2-d][1,3]oxazole were studied in a series of solvents. UV-Vis absorption spectra are insensitive to solvent polarity whereas the fluorescence spectra in the same solvent set show an important solvatochromic effect leading to large Stokes shifts. Linear solvation energy relationships were employed to correlate the position of fluorescence spectra maxima with microscopic empirical solvent parameters. This study indicates that important intramolecular charge transfer takes place during the excitation process. In addition, an analysis of the solvatochromic behavior of the UV-Vis absorption and fluorescence spectra in terms of the Lippert-Mataga equation shows a large increase in the excited-state dipole moment, which is also compatible with the formation of an intramolecular charge-transfer excited state. We propose both naphthoxazole derivatives as suitable fluorescent probes to determine physicochemical microproperties in several systems and as dyes in dye lasers; consequence of their high fluorescence quantum yields in most solvents, their large molar absorption coefficients, with fluorescence lifetimes in the range 1-3 ns as well as their high photostability. © 2013 The American Society of Photobiology.